The changing governance of UK flood management policies 1998-2010: a comparative analysis of local approaches in Scotland and England - Lafinhan, Dipo (2016)
The governments of Scotland and England have responded to the increase in flood risk by introducing legislation intended to manage present day flood risk and to avoid future flood risk. This thesis evaluates how the new policy regime has evolved and been implemented in Scotland and England, focusing particularly in Local Authorities, and using contrasts in rural and urban settings to reveal how the policy has had to be adapted to apply effectively in these different physical and administrative environments. Based on discourse theory and the institutionalisation features of policy networks, it is argued first that the new policy regime is subject to multiple interpretations and, second that policy change occurs as a result of the transformation of institutional practices of the multiple flood governance discourses by policy narratives in the policy process. The concept of the advocacy coalition framework is applied to reveal how contrasting local governance approaches result from continuous interactions between national policies and distinctive, local factors. These arguments are supported by the results of empirical research that examined policy change and local governance interpretation through textual analysis of relevant policy documents, interviews with key institutional stakeholders and participant observation of a local stakeholder meeting. Research findings reveal how the more pro-active local governance approaches serve as innovators in informing future national policies. This process stems from local interpretation of existing national policy through the mediating effects of distinctive local policy factors that result in the introduction of new policy ideas and actors. These ideas and the involvement of new actors are in turn transferred through revisions to national policies of flood risk governance. Consequently the policy mediating features of Local Authorities are manifest through first, the utility of policy narratives in driving national policy change and second, in shaping policies in local governance approaches.